Gambaran Self Efficacy Remaja Putri dalam Menghadapi Dismenore Primer - Rahmia Putri; Widia Lestari; Nurahannifah Rizky Tampubolon; Masrina Munawarah Tampubolon (Jurnal SMART Keperawatan, 2025)
Introduction:  The prevalence of dysmenorrhea in Indonesia is 64.25%, consisting of 54.89% primary dysmenorrhea and 9.36% secondary. Self-efficacy in adolescents had a significant influence on the way they deal with urgent situations, including in dealing with dysmenorrhea conditions. Objective: This study was conducted to describe the self-efficacy of adolescent girls in dealing with primary dysmenorrhea.  Methods: Quantitative research with a simple descriptive design and using a cross-sectional approach. The sample consisted of 86 respondents and used purposive nonprobability sampling techniques. Data were collected using the Pain Self Efficacy Questionnaire (PSEQ), this questionnaire consists of 10 items of questions about self-efficacy when experiencing pain. Results: Some respondents had moderate self-efficacy (40.7%), low self-efficacy (31.4%) and some respondents had high self-efficacy (27.9%) in dealing with primary dysmenorrhea. Conclusion: Most adolescent girls are able to manage pain and cope with dysmenorrhea well, but there are still some respondents who have a low level of self-efficacy. Adolescent girls are expected to increase literacy about pain management to increase self-efficacy in dealing with primary dysmenorrhea.